Identification and experimental validation of mitochondria-related genes biomarkers associated with immune infiltration for sepsis - Shu, Qi; She, Han; Chen, Xi; Zhong, Like; Zhu, Junfeng; Fang, Luo (Frontiers in Immunology, 2023)
Sepsis is a complex condition that is not yet fully understood with regards to its pathogenesis. Further research is necessary to identify prognostic factors, risk strati-fication tools, and effective diagnostic and therapeutic targets. Through analysis of three GEO datasets (GSE54514, GSE65682, and GSE95233), three different ex-pressed mitochondrial-related genes (DE-MiRGs) were identified as sepsis bi-omarkers. Using WGCNA and two machine learning algorithms, a significant dif-ference was observed in the immune microenvironment landscape between healthy controls and sepsis patients. Consensus clustering was subsequently performed to determine the molecular subtypes of sepsis, and the CIBERSORT algorithm was uti-lized to assess immune cell infiltration of samples. Of the DE-MiRGs, NDUFB3 was selected as a potential therapeutic target, as its significant elevated expression level was confirmed in sepsis using in vitro experiments and confocal microscopy, indi-cating its significant contribution to the mitochondrial quality imbalance in the LPS-simulated sepsis model. By investigating the role of these pivotal genes in im-mune cell infiltration, a better understanding of the molecular immune mechanism in sepsis was achieved, and potential intervention and treatment strategies were identified.